The Commodification of Childhood : The Children's Clothing Industry and the Rise of the Child Consumer - Cook, Daniel Thomas, 1961- (Book collections on Project MUSE., 2004)
Through a study of industry publications over much of the century, shows how the U.S. children's clothing industry produced increasingly refined categories of childhood.